2006
DOI: 10.21273/jashs.131.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Evaluation of a STELLA Software-based Daily CO2 Balance Model in Vitis vinifera L.

Abstract: This paper describes and evaluates the reliability of a model for prediction of daily carbon balance and dry matter (DM) accumulation in vertically shoot positioned grapevine (Vitis vinifera L.) canopies based on the user-friendly STELLA simulation software. Validation of the model was produced for potted 'Cabernet Sauvignon' grapevines at both low canopy density [LD (≈10 shoots/m of row)] and high canopy density [HD (≈20 shoots/m of row)] by comparing, ona seasonal basis, the modelled daily CO 2 balance with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 40 publications
8
34
0
1
Order By: Relevance
“…Ollat and Gaudillere (2000) reported a mean value of 1.2 mg carbon per gram dry mass per day for cv. Cabernet Sauvignon, and similar values were obtained for other cultivars (Poni et al 2006). Preliminary calculations showed that carbon depletion due to respiration (dRes/dt) is less than 2% of the carbon increment (C fl  dDW/dt), and, therefore, has minimal influence on simulated sugar concentration.…”
Section: Model Descriptionsupporting
confidence: 69%
See 1 more Smart Citation
“…Ollat and Gaudillere (2000) reported a mean value of 1.2 mg carbon per gram dry mass per day for cv. Cabernet Sauvignon, and similar values were obtained for other cultivars (Poni et al 2006). Preliminary calculations showed that carbon depletion due to respiration (dRes/dt) is less than 2% of the carbon increment (C fl  dDW/dt), and, therefore, has minimal influence on simulated sugar concentration.…”
Section: Model Descriptionsupporting
confidence: 69%
“…In most grape cultivars, glucose and fructose predominantly accumulate (Kliewer 1966;Liu et al 2006), although in peach, sucrose is predominant, and followed by glucose and fructose and minor amounts of sorbitol (Wu et al 2003). Based on these differences, the model parameters related to the rate of relative sugar metabolism were reduced from five in the SUGAR model to one, enabling the present model to be readily incorporated into grape models at the canopy scale (Gutierrez et al 1985;Poni et al 2006). The model's reproduction of the sugar concentration response to various conditions confirms that the conceptual framework proposed in the SUGAR model is generally applicable to fleshy fruits.…”
Section: Discussionmentioning
confidence: 78%
“…Consequently, the primary management schemes consist mostly in applying fungicides weekly or biweekly depending on cultivar susceptibility, history of anthracnose, and frequency of rain. However, leaf removal in the fruiting zone during the summer season is a common cultural practice in several grape producing areas (25). The observations made during this study on the severity of grape anthracnose support other reports on the capacity of E. ampelina to seriously damage grapevines with a maximum percent leaf area diseased of 86% and a maximum percent leaf defoliation of 68% recorded in 2006 (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The theoretical benefits of dynamic models (Costa et al, 2015;Moriondo et al, 2015) include their ability to capture nonlinear interactions between weather and viticulture, their basis on biological, causal processes and their potential to integrate the effects of climate with other factors including soil profiles, crop management practices, and perhaps most importantly for future climate change scenarios, the effects of elevated CO 2 levels on grapevine growth and development (Bindi et al, 1996;Poni et al, 2006).…”
Section: Limitations To Existing Approachesmentioning
confidence: 99%